Thermal behavior of spin-current generation in PtxCu1-x devices characterized through spin-torque ferromagnetic resonance - Wong, Grayson Dao Hwee (2021)
High temperature studies of spin Hall effect have often been neglected despite its profound significance in real-world devices. In this work, high temperature spin torque ferromagnetic resonance measurement was performed to evaluate the effects of temperature on the Gilbert damping and spin Hall efficiency of PtxCu1−x. When the temperature was varied from 300 K to 407 K, the Gilbert damping was relatively stable with a change of 4% at composition x = 66%. Alloying Pt and Cu improved the spin Hall efficiency of Pt75Cu25/Co/Ta by 29% to a value of 0.31 ± 0.03 at 407 K. However, the critical switching current density is dependent on the ratio between the Gilbert damping and spin Hall efficiency and the smallest value was observed when x = 47%. It was found that at this concentration, the spin transparency was at its highest at 0.85 ± 0.09 hence indicating the importance of interfacial transparency for energy efficient devices at elevated temperature.